2019
DOI: 10.1097/njh.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and Clinical Considerations in Treating Infections at the End of Life

Abstract: Patients often affirm the goal to pursue comfort at the end of life, although clinicians may struggle with how best to provide comfort and face the ethical dilemma of treating or allowing a suspected infection to unfold. Treating an infection at the end of life does not allow for uniform improvement in symptoms and more time with family and friends. Additionally, there is potential for burden to the patient or health care system and treatment may occur to the exclusion of other comfort measures. Currently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“…Many of the factors that may drive high antibiotic use in long-term care settings may also be reflected in the relatively low uptake of this policy; these include the increased infection risk in this population coupled with risk aversion from providers as well as perceptions that antibiotics are standard care and less burdensome than other therapies. 21,22,36,54,55 Whereas different providers have reported generally positive perceptions of antibiotic stewardship in qualitative studies, they also frequently mention pressures from patients or family to administer antibiotics. 54,56,57 Differences in the implementation rates of ASP policies might reflect variations in resource intensiveness, or NHs may have begun incrementally building their ASPs starting with policies for which resources were more readily accessible such as tracking antibiotics use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the factors that may drive high antibiotic use in long-term care settings may also be reflected in the relatively low uptake of this policy; these include the increased infection risk in this population coupled with risk aversion from providers as well as perceptions that antibiotics are standard care and less burdensome than other therapies. 21,22,36,54,55 Whereas different providers have reported generally positive perceptions of antibiotic stewardship in qualitative studies, they also frequently mention pressures from patients or family to administer antibiotics. 54,56,57 Differences in the implementation rates of ASP policies might reflect variations in resource intensiveness, or NHs may have begun incrementally building their ASPs starting with policies for which resources were more readily accessible such as tracking antibiotics use.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] NH residents are also at higher risk of adverse drug reactions, polypharmacy, and decreased antibiotic efficacy owing to altered pharmacokinetics. 13,[20][21][22] Through coordinated policies and practices, antibiotic stewardship programs (ASPs) seek to promote appropriate use of antibiotics in an effort to reduce adverse patient outcomes and to prevent resistance. Studies in acute care settings have found that ASPs can be effective at reducing these risks.…”
mentioning
confidence: 99%
“…Antimicrobials can cause harmful drug-drug interactions. Moreover, there is a higher risk of drug-resistant microorganisms and secondary infections (e.g., CDI) [ 67 , 68 , 69 ].…”
Section: Hais and Terminal Illnessmentioning
confidence: 99%
“…Es deseable que las instituciones habiliten programas específicos, con inclusión de comités de etica, tendientes a la protección del paciente y al empoderamiento de los profesionales al momento de definir determinaciones en este sentido, para que las actitudes a tomar no resulten un compendio de voluntades y creencias individuales, sujetas a amplia variabilidad y escasa reproducibilidad (104).…”
Section: ) Antibióticos Al Final De La Vidaunclassified